The Effect of Implementation of an Application-Based Archive System (SIS FORUM) on Employee Work Efficiency and Productivity at PT. Bumi Lingga Pertiwi Gresik (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to determine the effect of application-based filing system implementation (SIS FORUM) on employee efficiency and productivity and the variables that affect PT. Bumi Lingga Pertiwi Gresik. The method used in this study is a quantitative method using a saturated sample of 45 people. The research instrument is a validity and reliability test using simple linear regression. The design of this study is an explanation of the variables SIS FORUM (X), Efficiency (Y1), and Productivity (Y2). This research's limitations are limited to PT Bumi Lingga Pertiwi Gresik employees, so not generalizable to other populations. Future researchers are expected to be able to analyze the effect of more detailed variables related to the implementation or operation of the SIS FORUM system at PT. Bumi Lingga Pertiwi Gresik to become a reference or recommendation for the efficiency level of employee productivity. The results of this study indicate that (1) SIS FORUM implementation has a positive and significant effect on the work efficiency of employees at PT. Bumi Lingga Pertiwi Gresik; (2) SIS FORUM implementation positively and significantly impacts employees' work productivity at PT. Bumi Lingga Pertiwi Gresik. (3) SIS FORUM has an R2 (Adjusted R Square) value of 0.200, equivalent to 20%. It means that the influence of SIS FORUM on efficiency is 20%. The remaining 80% is influenced by other factors not examined. (4) SIS FORUM has an R2 (Adjusted R Square) value of 0.895, equivalent to 89.5%. It means that the influence of SIS FORUM on productivity is 89.5%. The remaining 10.5% is influenced by other factors not examined. Keywords: Efficiency, Productivity, SIS FORUM